Atypical Imaging Features of a Simple Intramuscular Lipoma - UMAMAGESWARI AMIRTHALINGAM (Journal of Clinical and Diagnostic Research, 2017)
Lipoma is a benign tumour of mesenchymal tissue which closely resembles normal fat even histologically but for its biochemical and ultrastructural differences. Simple lipoma presents as a mass which resembles fat on all the imaging modalities. Atypical lipoma, lipoma variants and liposarcoma show specific imaging features. We report this case due to the varied imaging appearance of a simple lipoma. A 52-year-old lady presented with history of swelling along the anterior aspect of thigh. Sonography, CT and MRI had done which revealed an atypical lipoma; however excision biopsy proved to be a simple lipoma.